Exploration and practice of nursing and health promotion programs in the outpatient department (门诊护理健康科普工作探索与实践) - LIU Yuichen (刘雨晨); REN Li (任丽); JIN Qi (金琦) (Journal of International Translational Medicine Limited, 2024)
Objective To establish a health promotion team consisting of nurses, and to carry out health promotion programs to improve the health care knowledge of patients in the outpatient clinic. Methods Health promotion programs including health education lectures, nursing health counseling, handbook of health-related knowledge and self-made videos were carried out, and the quality of the activities was continuously improved according to the evaluation outcomes. Results Participants' awareness of disease prevention and control had been enhanced after implementation of health promotion programs(P＜0. 05). Conclusion By taking advantage of workplace competence of nurses, nursing health promotion programs are effective to improve the disease prevention and control knowledge and self-protection ability of the population who had visited the outpatient clinic. (目的 通过组建护理健康科普队伍, 传播护理科学健康知识, 提高就诊患者的健康保健知识水平。方法 利用早、午间候诊时间段开展护理健康科普讲座、护理健康咨询、传递健康知识手册及自媒体视频等方式进行健康科普工作, 根据评价结果不断改进活动质量。结果 干预后, 参加护理健康科普讲座的受众者对相应讲座的健康知识掌握度优于干预前, 差异有统计学意义(P＜0. 05)。结论 通过开展护理健康科普, 发挥护士在健康科普工作中的专业优势, 有助于提高受众者的疾病防治知识水平和自我防护能力。)